1970
DOI: 10.3329/bjo.v15i1.4305
|View full text |Cite
|
Sign up to set email alerts
|

Techniques and results of stapedial surgery

Abstract: Abstract:Objective: To evaluate the improvement of hearing after stapedial surgery, to record the problems during surgery and to assess the complications of the same.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 4 publications
1
2
1
Order By: Relevance
“…Mean ± SD pre and post-operative air conduction was 54.88±3.43 dB and 29.52±3. 16 20 found that male (68.75%) was affected more by otosclerosis than female (31.25%) which was dissimilar to our finding. This difference may be due to lack of medical facilities in the remote part of the country.…”
Section: Resultscontrasting
confidence: 99%
See 2 more Smart Citations
“…Mean ± SD pre and post-operative air conduction was 54.88±3.43 dB and 29.52±3. 16 20 found that male (68.75%) was affected more by otosclerosis than female (31.25%) which was dissimilar to our finding. This difference may be due to lack of medical facilities in the remote part of the country.…”
Section: Resultscontrasting
confidence: 99%
“…Among them bilateral otosclerosis was common. Almost similar finding was observed by Xie J et al 21 Fakir et al 20 found deafness (100%), tinnitus (75%) and vertigo (25%) in their study which was almost similar to our study. Souza et al 1 reported that unilateral (71.2%) otosclerosis was more common than bilateral which was dissimilar to our finding.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…This difference may be due to demographic variation. Regarding the occupation in the study population were service holders, housewives and students 18 .…”
Section: Discussionmentioning
confidence: 99%